Plato's Sun : an Introduction to Philosophy. - Lawless, Andrew (University of Toronto Press, 2005)
In Plato's Sun, Andrew Lawless takes on the challenge of creating an introductory text for philosophy, arguing that such a work has to take into account of the strangeness of the field and divulge it, rather than suppress it beneath traditional certainties and authoritative pronouncements.